EFFICACY OF ULTRAVIOLET RADIATION ON SECONDARY WHITE MARKINGS AFTER COLOR IRONING (Conference Zone, 2022)
In many young men and women, especially during adolescence and adolescence, and in adults, white and brown spots of various shapes and sizes appear on the neck, shoulders, chest, armpits, and rarely on the legs, abdomen, and hair on the head. will come The color of the spots is different: from pink-yellow to dark-brown, often reminiscent of the color of milk and coffee.